Linguistic attitudes in Peru: The predominance of Spanish in the Central and Northern Coast - Arias Torre, Ana (2012)
This article is a summary of the results of the study of linguistic attitudes in Peru with special emphasis on Metropolitan Lima and is based on four hundred interviews scattered through the different districts of the Province of Lima and Callao. This study forms part of the LIAS proyect (Linguistic Identity and Attitudes in Latin America) and is financed by the Faculty of Foreign Languages of the University of Bergen, Norway.